結果
問題 | No.898 tri-βutree |
ユーザー |
![]() |
提出日時 | 2019-10-04 23:53:22 |
言語 | C++17 (gcc 13.3.0 + boost 1.87.0) |
結果 |
WA
|
実行時間 | - |
コード長 | 2,235 bytes |
コンパイル時間 | 2,870 ms |
コンパイル使用メモリ | 208,288 KB |
最終ジャッジ日時 | 2025-01-07 20:54:12 |
ジャッジサーバーID (参考情報) |
judge3 / judge1 |
(要ログイン)
ファイルパターン | 結果 |
---|---|
sample | AC * 1 |
other | AC * 1 WA * 20 |
ソースコード
#include<bits/stdc++.h>using namespace std;template< typename G >struct DoublingLowestCommonAncestor {const int LOG;vector< int > dep;const G &g;vector< vector< int > > table;DoublingLowestCommonAncestor(const G &g) : g(g), dep(g.size()), LOG(32 - __builtin_clz(g.size())) {table.assign(LOG, vector< int >(g.size(), -1));}void dfs(int idx, int par, int d) {table[0][idx] = par;dep[idx] = d;for(auto &to : g[idx]) {if(to != par) dfs(to, idx, d + 1);}}void build() {dfs(0, -1, 0);for(int k = 0; k + 1 < LOG; k++) {for(int i = 0; i < table[k].size(); i++) {if(table[k][i] == -1) table[k + 1][i] = -1;else table[k + 1][i] = table[k][table[k][i]];}}}int query(int u, int v) {if(dep[u] > dep[v]) swap(u, v);for(int i = LOG - 1; i >= 0; i--) {if(((dep[v] - dep[u]) >> i) & 1) v = table[i][v];}if(u == v) return u;for(int i = LOG - 1; i >= 0; i--) {if(table[i][u] != table[i][v]) {u = table[i][u];v = table[i][v];}}return table[0][u];}};vector<int> wei;void dfs(vector<vector<pair<int,int>>>& g, int v, int p){for(auto e : g[v]){if(e.first == p) continue;wei[e.first] += (e.second + wei[v]);dfs(g, e.first, v);}}int main(){int N;cin >> N;vector<vector<int>> G(N);vector<vector<pair<int,int>>> g(N);wei.assign(N, 0);for(int i = 0; i < N-1; i++){int u,v,w;cin >> u >> v >> w;G[u].emplace_back(v);G[v].emplace_back(u);g[u].emplace_back(make_pair(v,w));g[v].emplace_back(make_pair(u,w));}dfs(g, 0, -1);DoublingLowestCommonAncestor<vector<vector<int>>> lca(G);lca.build();int Q, x, y, z;cin >> Q;for(int i = 0; i < Q; i++){cin >> x >> y >> z;int a = lca.query(x, y);int b = lca.query(x, z);int c = lca.query(y, z);int W = 0;W += (wei[x] - wei[a]) + (wei[y] - wei[a]);W += (wei[x] - wei[b]) + (wei[z] - wei[b]);W += (wei[y] - wei[c]) + (wei[z] - wei[c]);W /= 2;cout << W << endl;}}